Interleukin-6 in Critical Coronavirus Disease 2019, a Driver of Lung Inflammation of Systemic Origin? - Nikolai Ravn Aarskog, MD (Wolters Kluwer, 2021)
OBJECTIVES:. To examine whether interleukin-6 in critical coronavirus disease 2019 is higher in arterial than in central venous blood, as a sign of predominantly local pulmonal rather than systemic interleukin-6 production. DESIGN:. Prospective cohort pilot study with repeated weekly measurements of interleukin-6 in arterial and central venous blood. Respiratory function, assessed with Pao2/Fio2 ratio, was measured at the time of blood sampling. SETTING:. ICU at a university hospital. SUBJECTS:. Nine adult patients with critical coronavirus disease 2019, actively treated and receiving mechanical ventilation. MEASUREMENTS AND MAIN RESULTS:. No difference between arterial and central venous interleukin-6 was found. There was a significant negative relationship between interleukin-6 concentration and P/F ratio in both arterial (p = 0.04) and central venous (p = 0.03) blood. CONCLUSIONS:. The absence of an arteriovenous interleukin-6 difference implies that interleukin-6 in critical coronavirus disease 2019 is mainly produced outside the lungs as part of a systemic inflammatory response syndrome and act as a driver of local inflammation and damage in the lungs.